(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Since students utilize time management every day, it is crucial for people to learn how to manage their time effectively. It’s crucial to manage the Grade 11 students’ schedule so they may complete their assignments on time and refrain from procrastinating. Effective time management is necessary to improve students’ academic performance and achievements. Every student should be able to manage their time effectively, which includes setting goals and priorities, making use of time management tools, and maintaining organization. This research found that 93.9% of the 50 respondents were 16-18 years old, and most of the genders were male. Subproblem No. 1 found that 93.9% of the respondents were aged 16-18, and most of the gender was male. Subproblem No. 2 found that the problems encountered in meeting the deadlines were distractions, and the majority agreed that tasks were the most effective in meeting the deadlines. The researchers concluded that the result of the study is based on facts that were gathered from the respondents and represent the Utilization of time management in meeting deadlines.